Highlights from the International Summit on Intellectual Disability and Dementia Implications for Brazil - Santos, Flavia H. [UNESP]; Watchman, Karen; Janicki, Matthew P. (Associação de Neurologia Cognitiva e do Comportamento, 2018)
In October of 2016, an interdisciplinary group representing North and South American and European countries met in Glasgow, Scotland, to scrutinize universal issues regarding adults with intellectual disability (ID) affected by dementia and to produce recommendations and guidelines for public policy, practice, and further research. The aim of this paper is to apprise relevant outcomes of the Summit targeting Brazilian researchers, clinicians, and nongovernmental organizations in the field of ageing and dementia that are committed to developing the Brazilian national dementia plan. Three core themes were covered by the Summit: i) human rights and personal resources, ii) personalized services and caregiver support, and iii) advocacy and public impact. The exploration of the themes highlighted variations across countries, and revealed consensual views on matters such as international networks, guidance for practices, and advocacy on behalf of both people with ID affected by dementia, and their families. The authors outline the challenges Brazil must confront regarding ageing and dementia and proffer recommendations to address the needs of adults with ID affected by dementia within this scenario; both of which would help in developing the Brazilian national dementia plan.

Em outubro de 2016, um grupo interdisciplinar representando países da América do Norte e do Sul, bem como Europeus reuniu-se em Glasgow, na Escócia, para examinar questões relativas aos adultos com deficiência intelectual (DI) afetados por demência e para produzir recomendações e diretrizes referentes às políticas públicas, práticas e pesquisa. O objetivo deste artigo é informar os resultados relevantes da Cúpula aos pesquisadores, clínicos e organizações não-governamentais brasileiras que atuam no campo do envelhecimento e da demência, e estão envolvidos no desenvolvimento do plano nacional de demência. Três temas centrais foram discutidos na Cúpula: i) Direitos humanos e recursos pessoais, ii) Serviços personalizados e apoio aos cuidadores, e iii) Advocacia e impacto público. A exploração dos temas destacou as variações entre os países e revelou visões consensuais em questões como redes internacionais, orientação para práticas e defesa de direitos em nome de pessoas com DI afetadas por demência e suas famílias. Os autores descrevem os desafios que o Brasil deve enfrentar em relação ao envelhecimento e à demência e apresentam recomendações para atender às necessidades de adultos com DI afetados por demência nesse cenário; ambos aspectos contribuem para o desenvolvimento do plano nacional de demência.
SÍNTESE DA CÚPULA INTERNACIONAL SOBRE DEFICIÊNCIA INTELECTUAL E DEMÊNCIA: IMPLICAÇÕES PARA O BRASIL
Keywords: dementia; Down syndrome; intellectual disability; national plan; summit; demência; síndrome de Down; deficiência intelectual; plano nacional; cúpula